Digital Parenting from an Islamic Educational Perspective as a Strategy to Address Gadget Addiction in Children - azzahra Wiyono; Usvatun Khasanah; Sekar Galuh Putri Wiseno; Abdussyukur (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2026)
Rapid digital transformation has changed parenting patterns, marked by the increasing use of gadgets from an early age, which has the potential to lead to addiction. This study aims to analyze the concept of digital parenting based on Islamic education, identify the causes and impacts of gadget addiction in children, and formulate effective and Islamic-based implementation strategies. The study used a descriptive qualitative approach with a literature review method, sourced from the Qur'an, hadith, scientific journals, books, and reports from official institutions. The results of the study indicate that gadget addiction in children is a multidimensional phenomenon influenced by internal, situational, social, and external factors. Its impacts include psychological disorders, physical health, and decreased social interaction, despite the potential for positive aspects in education, communication, and creativity. From an Islamic education perspective, digital parenting emphasizes the integration of Islamic values such as role models (uswah hasanah), supervision (hisbah), self-reflection (muhasabah), and balance (tawazun). Implementation strategies include limiting gadget use, active mentoring, habituating religious activities, increasing parental digital literacy, and utilizing educational applications. Thus, Islamic digital parenting is a comprehensive approach that can overcome gadget addiction while simultaneously shaping children's character with noble morals in the digital era